PREFERENSI PERENCANAAN PAJAK BENTUK USAHA: STUDI KASUS PADA WAJIB PAJAK PERORANGAN DI KOTA BITUNG - Wantah, Roj Jongke; Kalangi, Lintje; Budiarso, Novi Swandari (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2023)
There is a phenomenon gacor5000 that occurs where individual entrepreneurs tend to choose (preference) the form of business entity as part of their tax planning. The corporate form of business is considered more profitable than an individual business when the owned business begins to grow larger. The increase in business turnover which causes changes in tax administration obligations in terms of tariffs and bookkeeping obligations is estimated to be the cause of individual entrepreneurs tending to choose businesses in the form of entities.Based on data compiled from KPP Pratama Bitung, it shows that there are 14 individual taxpayers who have changed their form of business during the last 5 year confinement from 2016 to 2021. From the previous total of Rp.44.821.482 to a total of Rp. 1.115.636.  This study aims to know the preferences of individual taxpayers in conducting tax planning for the selection of business forms. This study uses a qualitative method with a case study approach. The selected informants were 10 individual business owners were a concern 10  in tax planning for the selection of business forms with the 3 people having switched during the research, while the rest had not switched. The data were obtained through observation techniques, in-depth interviews and documentation studies.The results of the study show that entrepreneurs as taxpayers always try to take advantage of every situation and rule to pay as little tax as possible in order to save expenses and maximize business profits, so that the decision to transfer the form of business with tax planning is carried out in order to get maximum profit without violating applicable regulations gacor5000.